Who invented home video games? Ralph Baer - Carson, Mary Kay. (Berkeley Heights, NJ : Enslow Elementary, 2012)
Learn about Ralp Baer, and see how he invented video games.
Includes bibliographical references (p. 22-23) and index.
2.7
K-3
K-3
Keywords: Baer, Ralph H. -- Juvenile literature; Baer, Ralph H; Baer, Ralph H; Electrical engineers -- United States -- Biography -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature; Video games -- History -- Juvenile literature; Electrical engineers; Inventors; Video games -- History; Electrical engineers -- Biography; Inventors -- United States -- Biography; Video games -- History